JUDGEMENT IN DEFAULT – WAS THE COMPROMISE FINALLY FOUND? - Nekrošius, Vytautas (Teisė, 2017)
In this article the author analyses the amendment of the Code of the Civil Procedure of the Republic of Lithuania, adopted on the 8th of November, 2016, which is related to the improvement of the procedure of judgement in default. The author is trying to answer the question whether the long lasting dispute between legal scholars and practitioners about the scope of the assessment of evidence is finally resolved.